The Effect of Financial Attitudes on Financial Behavior with Financial Self-Efficacy as a Mediating Variable - Khusaini, Imron Nur; Anwar, Muhadjir (PT FORMOSA CENDEKIA GLOBAL, 2023)
Individuals need to manage and make decisions on their personal finances in order to meet their needs and have good financial behavior for good financial goals. Financial self-efficacy theory was studied to see the effect of financial attitudes on financial behavior. This study was conducted with the aim of: a) to determine the effect of financial attitudes on financial behavior in Management Students of UPN